Experimental and analytical study of an innovative integrated dual-source evaporator for solar-assisted heat pumps. (December 2019) - Simonetti, Riccardo; Molinaroli, Luca; Manzolini, Giampaolo
Highlights: Experimental and numerical analysis were carried out in order to confirm the concept. The optimal configuration between six different circuitries was numerically found. In a wide operating range the panels production overcomes the heat pump consumptions. A coefficient of performance higher than 14% was found respect to air-source machine. Abstract: Energy efficiency is an effective way to produce energy reducing the impact of fossil fuels in the energy sector. A promising solution for residential application consists of producing domestic hot water and space heating using Solar-Assisted Heat Pump. This work analyzes the performance of a Solar-Assisted Heat Pump with an innovative Integrated Dual-Source Evaporator connected to Photovoltaic/Thermal modules. The concept is firstly validated in laboratory where the Solar-Assisted Heat Pump is operated in real environmental conditions. Then, a numerical model is developed in Matlab® to identify the optimal design of the Integrated Dual-Source Evaporator. Numerical results show that the performance of the system are significantly affected by the solar irradiance and in a wide operating range the photovoltaic production overcomes the Heat Pump consumptions. Compared to a standard Air-Source Heat Pump, the proposed concept shows up to 14% higher Coefficient of Performance.